Willingness to Use Pre-exposure Prophylaxis (PrEP) and Preferences Among Men Who have Sex with Men in Mumbai and Chennai, India: A Discrete Choice Experiment. - Chakrapani, Venkatesan; Newman, Peter A.; Cameron, Michael; Shunmugam, Murali; Roungprakhon, Surachet; Rawat, Shruta; Baruah, Dicky; Nelson, Ruban; Tepjan, Suchon; Scarpa, Riccardo (AIDS & Behavior, 2021)
Pre-exposure prophylaxis (PrEP) programs are planned for key populations in India. We examined PrEP awareness and willingness to use PrEP in order to support products and services for MSM. From December 2016 to March 2017, we conducted a survey and discrete choice experiment (DCE)—a technique to quantify the strength of participants' trade-off preferences among various product attributes—to assess willingness to use PrEP and related preferences. MSM were recruited from cruising sites and HIV prevention services in Mumbai and Chennai. DCE data were analyzed using mixed logit regression models and estimated marginal willingness-to-pay, the relative value participants' place on different PrEP attributes. Overall, 76.6% indicated willingness to use PrEP. Efficacy had the greatest effect on choice (high vs. moderate, aOR = 19.9; 95% CI 13.0–30.4), followed by dosing frequency (intermittent vs. daily regimen, aOR = 2.02; 95% CI 1.8–2.2). Participants preferred no (vs. minor) side-effects, subsidized (vs. market) price, and government (vs. private) hospitals. Findings suggest that educational and social marketing interventions should emphasize PrEP's high efficacy and minimal side effects, and programs should provide government-subsidized PrEP with choices of intermittent or daily dosing delivered by government and private hospitals/clinics in order to optimize PrEP uptake among MSM in India.